A Study of the Effect of Kaolin as a Fuel Oil Additive on the Corrosion Inhibition of Fireside Superheater Boiler Tubes - Ali, Alaa’ Mshjel (Al-Khwarizmi Engineering Journal, 2010)
The objective of the present study is to determine the effect of Kaolin as a fuel oil additive to minimize the fireside corrosion of superheater boiler tubes of ASTM designation (A213-T22) by increasing the melting point of the formed slag on the outside tubes surface, through the formation of new compounds with protective properties to the metal surface. The study included measuring corrosion rates at different temperatures with and without additive use with various periods of time, through crucible test method and weight loss technique. A mathematical model represents the relation between corrosion rate and the studied variables, is obtained using statistical regression analysis. Using this model, the best additive to ash weight ratio was specified. Then scanning electron microscopic images taken to the two treated and untreated samples with additive to study the difference in nature of slag formed on the metal surface to the two cases.